Åndsforestillinger og deres enhed i Johannesevangeliet - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2018)
Inspired by recent developments in Johannine research in Denmark, this article investigates the coherence of the concept of pneuma and paraklêtos in the Johannine writings. On the basis of the clear difference between pneuma and paraklêtos in First John, it differentiates between three different concepts in the Fourth Gospel. The first concerns Jesus’ possession of the pneuma from the incarnation to the death on the cross. It derives from the synoptic tradition, or more probably directly from the Gospel of Mark. The second does not have parallels in the synoptic gospels. It concerns the role of the pneuma for the believers. All instances are connected with the ritual praxis in the community and have remarkable relations to Paul. The third conception includes the Paraclete-sayings and is probably a genuine Johannine invention. It presents the pneuma-paraclete as an active figure that takes the place of the absent Jesus and in many ways authorizes the gospel writing. It is furthermore argued that the logos of the prologue can be understood in specific Stoic terms. The Stoic understanding of logos as being the cognitive side of the material pneuma is able to comprise all aspects of the Johannine pneuma-paraclete even if it is a combination of different ideas. Therefore, the prologue should be understood as a philosophical introduction that makes the reader incorporate all three Johannine pneumata into one conception.